Protein X-ray crystallography of the 14-3-3ζ/SOS1 complex - Ballone, Alice (Data Brief, 2018)
Activation of Ras-MAPK signaling regulates essential cellular functions; its aberration leads to irregular cell proliferation and differentiation (i.e. pancreatic cancer). Previously, it was revealed that the formation of the complex of the 14-3-3 protein and the Son of sevenless homolog 1 (SOS1) - one of the main actors of the Ras-MAPK cascade -, would represent a key-process to downstream the deviant Ra-MAPK signaling. In this data article we attempt to shed some light on the 3D structure, providing useful details about the crystallization process of the 14-3-3ζ dimer in complex with the 13-mer SOS1pS(1161). The crystal structure is deposited at the Protein Data Bank with identifier 6F08. This Data in Brief article refers to “Structural characterization of 14-3-3ζ in complex with the human Son of sevenless homolog 1 (SOS1) (2018).”